Du Pont System Analysis To Assess The Company’S Financial Performance (Case Study Of a Coal Sub-Sector Mining Company For The 2018-2022 Period) - Nurul Shoidah (Indonesian Development of Economics and Administration Journal, 2023)
The purpose of this study is to determine the financial performance of coal mining companies using the Du Pont System. The analysis method uses Du Pont System with variables, namely Total Asset Turnover (TATO), Net Profit Margin (NPM), and Return On Investment (ROI). This research was conducted with a quantitative descriptive approach. The data used is secondary data in the form of financial statements. The results of the study using Du Pont System showed that one company with a variable Net Profit Margin that was above the industry average of % was PT Golden Energy Mines Tbk of 27.8%, and four companies with a variable Net Profit Margin that was below the industry average. Total Asset Turnover and multiplier equity ratio are still below the industry standard average. And for the assessment of return on investment du pond, only one company whose value is above 30%, namely PT Golden Energy Mines Tbk at 57.99% and four other companies are still below industry standards. And for the assessment of return on equity du pond 5 companies that are the object of research still have values below industry standards so that it can be said that the company’s efficiency in managing all assets to generate profits is not good enough.